Dinamika Inflasi, Suku Bunga, dan Pertumbuhan Ekonomi Jawa Timur: Analisis Empiris Periode 2011–2024 - Syafa Salsabella; Siti Nur Qomariyah; Azhar Irfana Gangsar (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah, 2026)
Economic growth is a key indicator of regional development success, influenced by various macroeconomic factors, including inflation and interest rates. This study aims to analyze the impact of inflation and interest rates on the economic growth of East Java Province during the 2011–2024 period. A quantitative approach was employed using secondary data from Statistics Indonesia (BPS) and Bank Indonesia (BI). The analysis utilized classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that inflation has a positive but insignificant effect (coefficient: 0.196; significance: 0.173), whereas interest rates have a positive and significant effect (coefficient: 0.294; significance: 0.044). Simultaneously, both variables exert a significant influence, with a significance value of 0.015 and an R-squared value of 0.537. The findings suggest that interest rates play a more substantial role than inflation in influencing economic growth in East Java.